1997
DOI: 10.1074/jbc.272.31.19408
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphorylation of Bovine DNase I Asn-linked Oligosaccharides Is Dependent on Specific Lysine and Arginine Residues

Abstract: The secretory glycoprotein DNase I acquires mannose 6-phosphate moieties on its Asn-linked oligosaccharides, indicating that it is a substrate for UDP-GlcNAc:lysosomal enzyme N-acetylglucosamine-1-phosphotransferase (phosphotransferase) (Cacia, J., Quan, C., and Frenz, J. (1995) Glycobiology 4, 99). Phosphotransferase recognizes a conformation-dependent protein determinant that is present in lysosomal hydrolases, but absent in most secretory glycoproteins. To identify the amino acid residues of DNase I that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…A number of studies from our laboratory and others have shown that the protein recognition domain of acid hydrolases is a complex conformation-dependent determinant that includes a number of critical lysine residues (16)(17)(18)(19)(20)(21)(22)(23). On this basis, it seems likely that the interaction of an acid hydrolase with GlcNAc-1-phosphotransferase would involve multiple contacts between the surfaces of the two proteins.…”
mentioning
confidence: 99%
“…A number of studies from our laboratory and others have shown that the protein recognition domain of acid hydrolases is a complex conformation-dependent determinant that includes a number of critical lysine residues (16)(17)(18)(19)(20)(21)(22)(23). On this basis, it seems likely that the interaction of an acid hydrolase with GlcNAc-1-phosphotransferase would involve multiple contacts between the surfaces of the two proteins.…”
mentioning
confidence: 99%
“…for lysine in some contexts (15)(16)(17). Other residues in the vicinity of critical lysine residues may affect the accessibility or properties of the lysine residues.…”
Section: Discussionmentioning
confidence: 99%
“…The chimeric studies of cathepsin D, as the authors note, can be interpreted by having two independent phosphorylation signals, instead of having a single extended signal (9). The existence of two or more signals on cathepsin D explains why mutation of individual lysine residues affects phosphorylation of the two cathepsin D oligosaccharides differently and why localized phosphorylation of engineered glycosylation sites was not observed for this protein (12,15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The abbreviations used are: ER, endoplasmic reticulum; M6P, mannose-6-phosphate; ASA, arylsulfatase A; ASB, Arylsulfatase B; ASE, arylsulfatase E; ASU, sea urchin arylsulfatase; BHK, baby hamster kidney; HPLC, high-performance liquid chromatography; MALDI-TOF, matrix-assisted laser desorption ionization time-of-flight. enzymes (8,11,14), suggesting that the spacing of surface lysines is critical for phosphotransferase recognition (8).…”
mentioning
confidence: 99%